Working Capital Management and Profitability of Dabur Nepal Private Limited - Sah, Gunanand; Shrestha, Binay (Journal of Economics and Management, 2025)
This paper examines the impact of working capital management on the profitability of Dabur Nepal Pvt. Ltd. over a ten-year period from FY 2015/16 to FY 2024/25. The research adopts a descriptive and analytical design, relying exclusively on secondary data extracted from company financial statements and its website. Key working capital components—Inventory Conversion Period (ICP), Receivable Conversion Period (RCP), Payable Deferral Period (PDP), and Cash Conversion Period (CCP)—serve as independent variables, while Return on Assets (ROA) represents the dependent variable. Statistical tools such as correlation and regression analyses were employed to explore the relationships between these variables. The descriptive results revealed that the company’s mean ROA was 7.94%, with moderate variability, and the mean ICP, RCP, PDP, and CCP were 137.85, 73.85, 76.31, and 135.38 days, respectively. Correlation analysis indicated that ROA was positively correlated with ICP but negatively correlated with RCP, PDP, and CCP, suggesting that longer collection and payment cycles may adversely affect profitability. However, regression results showed that the model was not statistically significant (R² = 0.118, p = 0.847), implying that these working capital variables collectively explain only a small portion of ROA variation. The study concludes that while working capital components exhibit some association with profitability, their combined effect on ROA is minimal. It recommends expanding future research to include multiple firms across sectors, larger datasets, and additional financial variables to gain deeper insights into the relationship between working capital efficiency and corporate profitability in Nepal’s manufacturing sector.